2013
DOI: 10.1186/1471-2474-14-18
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage collagen damage in hip osteoarthritis similar to that seen in knee osteoarthritis; a case–control study of relationship between collagen, glycosaminoglycan and cartilage swelling

Abstract: BackgroundIt remains to be shown whether OA shares molecular similarities between different joints in humans. This study provides evidence for similarities in cartilage molecular damage in osteoarthritic (OA) joints.MethodsArticular cartilage from osteoarthritic hip joints were analysed and compared to non-OA controls regarding collagen, glycosaminoglycan and water content. Femoral heads from 16 osteoarthritic (OA) and 20 reference patients were obtained from hip replacement surgery due to OA and femoral neck … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 43 publications
(46 reference statements)
7
33
0
1
Order By: Relevance
“…In the OA study, simulation results showed an increment of cartilage swelling for advanced grades of OA disease. This has recently been confirmed experimentally [2,56], and associated with weakening of the collagen network and subsequent reduction of PG content. The results obtained here show that changes in mechano-electrochemical properties of the matrix may serve as a biomarker for progression of cartilage degeneration, making the present model a helpful tool to predict the behaviour and therefore the degree of tissue degeneration, thus avoiding complex chemical analyses of the subsequent extraction of cartilage.…”
Section: Resultsmentioning
confidence: 71%
“…In the OA study, simulation results showed an increment of cartilage swelling for advanced grades of OA disease. This has recently been confirmed experimentally [2,56], and associated with weakening of the collagen network and subsequent reduction of PG content. The results obtained here show that changes in mechano-electrochemical properties of the matrix may serve as a biomarker for progression of cartilage degeneration, making the present model a helpful tool to predict the behaviour and therefore the degree of tissue degeneration, thus avoiding complex chemical analyses of the subsequent extraction of cartilage.…”
Section: Resultsmentioning
confidence: 71%
“…However, the percentage of degraded collagen in the tissue, as measured using chymotrypsin digestion, and in the synovial fluid, as measured using the C2C assay, was increased. Previous studies have also shown increased collagen degeneration in OA tissue using chymotrypsin digestion (Bank et al, 1997; Hosseininia et al, 2013). Our findings highlight the complexity of factors and interactions that contribute to the T2 relaxation time.…”
Section: Discussionmentioning
confidence: 87%
“…In order to solubilize extractable or cleaved collagen in the tissue, the second half of each explant was digested overnight in 1 mg/mL α-chymotrypsin (Sigma) at 37 °C (Hosseininia et al, 2013). After chymotrypsin digestion, the supernatant was collected and stored at −20 °C and the remaining tissue was papain digested overnight at 65 °C (Rowland et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Hydroxyproline which is one of the three major amino acids present in the collagen protein chain is frequently used to estimate the total collagen content in samples (Hosseininia et al, 2013;McAlinden et al, 2014). The amount of collagen in the cartilage powders averaged 72.9% weight/dry weight (w/dw) in adult articular cartilage, 64.1% w/dw in young articular cartilage and 41.5% w/dw in nasal cartilage.…”
Section: Biochemical Assessment Of Powdersmentioning
confidence: 99%